6x-48=5x

Simple and best practice solution for 6x-48=5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-48=5x equation:


Simplifying
6x + -48 = 5x

Reorder the terms:
-48 + 6x = 5x

Solving
-48 + 6x = 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
-48 + 6x + -5x = 5x + -5x

Combine like terms: 6x + -5x = 1x
-48 + 1x = 5x + -5x

Combine like terms: 5x + -5x = 0
-48 + 1x = 0

Add '48' to each side of the equation.
-48 + 48 + 1x = 0 + 48

Combine like terms: -48 + 48 = 0
0 + 1x = 0 + 48
1x = 0 + 48

Combine like terms: 0 + 48 = 48
1x = 48

Divide each side by '1'.
x = 48

Simplifying
x = 48

See similar equations:

| 5=x+3-(3x) | | -27=4x-17 | | -(8x-4)-(5x-6)+7=-12(x-1)-(4x+13)+3 | | 40=2x^2-6x | | 2y-4+16=5y-9 | | 12b+6(3-b)=b+3 | | -5=2x^2-6x | | (2+j)(3+j)(4+j)= | | 6+3t=8 | | 4(-3x+11)=-10(x-4)-14x | | P=200q+-4q | | 6x-13-14x=6x-8 | | -4x+5-7+9x= | | y=2x+7graphed | | -9(8x+4)=24 | | 6(x+2)-2x=4(x+3) | | -5(2y-8)-y=-4(y-3) | | (x-7.5)(x+4.3)=0 | | P=(100-2q)2q | | -9(8x+4)=27 | | 6(x+2)=3(2x+5) | | 9(9x-5)-3x= | | Y=2x-10x+8 | | W^2+4w+6=0 | | 3(x+6)-1=21-5x-4+8x | | -6x^2-5x+4=0 | | 1.6h-72=4d-30 | | 4(-7x+1)=88 | | mx=3+15x | | -4x+2-5x-2(6x-1)+11=4(x+5)+12-7-3x | | 14+7x=49 | | 5x+(5x-5)=25 |

Equations solver categories